2016
DOI: 10.1117/1.jbo.21.5.056005
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral fluorescence imaging of human ovarian and fallopian tube tissue for early-stage cancer detection

Abstract: With early detection, 5-year survival rates for ovarian cancer exceed 90%, yet no effective early screening method exists. Emerging consensus suggests over 50% of the most lethal form of the disease originates in the fallopian tube. Twenty-eight women undergoing oophorectomy or debulking surgery provided informed consent for the use of surgical discard tissue samples for multispectral fluorescence imaging. Using multiple ultraviolet and visible excitation wavelengths and emissions bands, 12 fluorescence and 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 49 publications
(82 reference statements)
0
18
0
Order By: Relevance
“…[19][20][21][22][23][24][25] Laser sources are used for the endoscope prototype and are similar in central wavelength to those provided by a filtered xenon arc lamp in our previous MFI imaging study on ex vivo ovarian and fallopian tube tissue. 25 The ultraviolet and blue wavelengths efficiently excite the endogenous fluorophores. Sampling the blood absorption curve in reflectance mode with 375, 406, and 515 nm can also provide diagnostic utility.…”
Section: Optical Designmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25] Laser sources are used for the endoscope prototype and are similar in central wavelength to those provided by a filtered xenon arc lamp in our previous MFI imaging study on ex vivo ovarian and fallopian tube tissue. 25 The ultraviolet and blue wavelengths efficiently excite the endogenous fluorophores. Sampling the blood absorption curve in reflectance mode with 375, 406, and 515 nm can also provide diagnostic utility.…”
Section: Optical Designmentioning
confidence: 99%
“…Endogenous fluorescence differences among normal, benign, and cancerous ovarian tissues have been characterized both in vivo and ex vivo by investigators and others using fiber-optic probes [19][20][21][22] and widefield autofluorescence imaging. [23][24][25] Mutispectral fluorescence imaging (MFI) can image in both reflectance and fluorescence mode to either measure optical absorption or fluorescence emission, both of which can be an indicator of molecular changes (changes in concentration of hemoglobin or fluorophores) or to combine multiple reflectance images for pseudo-white-light imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Methods with a finer sampling of the spectral response, such as multi-or hyperspectral imaging (MSI/HSI) systems (≈10 and 100 spectral color channels, respectively), 12,13 may enable quantitative assessment of functional tissue properties and more detailed statistical classification of the spectral changes that occur during disease. The use of reflectance-based MSI/HSI systems in biomedical applications has, for example, been shown to increase contrast in vascular conditions, 14 wound healing, [15][16][17] ophthalmology, 15,18,19 cancer diagnostics, 12,[20][21][22][23] and for the determination of tumor resection margins. 24 The application of a targeted fluorescent contrast agent is often referred to as optical molecular imaging (OMI) and has shown promise for endoscopic cancer detection in the GI tract.…”
Section: Introductionmentioning
confidence: 99%
“…26 It was shown that fluorescence imaging of human ovarian and fallopian tube tissue is promising for early cancer detection. 27 A combination of fluorescence-based techniques and OCT seems to provide additional benefits. [28][29][30] An endoscopic probe for the conjugation of OCT with wide-field falloposcopy 31 , as well as multimodal imaging of ovarian tissue using OCT and second-harmonic generation microscopy, was also reported.…”
Section: Customization Of Optical Coherence Tomography Probes For Gynmentioning
confidence: 99%